A one‐dimensional manganese(III)–porphyrin coordination polymer: crystal structure and photophysical properties. Issue 5 (8th April 2020) - Chen, Wen-Tong
Abstract : A novel one‐dimensional coordination polymer was synthesized from manganese(III) and 5, 10, 15, 20‐tetrakis(pyridin‐3‐yl)‐21 H, 23 H ‐porphine. The chains are further connected through C—H…Cl interactions, forming a two‐dimensional network. This polymer shows a red photoluminescence that originates from ligand‐to‐ligand charge transfer (LLCT) with partial metal‐to‐ligand charge transfer (MLCT), as revealed by TDDFT theoretical calculations. Abstract : A novel manganese(III)–porphyrin complex, namely, catena ‐poly[[chloridomanganese(III)]‐μ2 ‐5, 10, 15, 20‐tetrakis(pyridin‐3‐yl)‐21 H, 23 H ‐porphinato(2−)‐κ 5 N 21, N 22, N 23, N 24 : N 5 ], [MnCl(C40 H24 N8 )] n, 1, was prepared by the hydrothermal reaction of manganese chloride with 5, 10, 15, 20‐tetrakis(pyridin‐3‐yl)‐21 H, 23 H ‐porphine. The crystal structure was determined by single‐crystal X‐ray diffraction. The porphyrin macrocycle exhibits a saddle‐like distortion geometry. The Mn III atom has a six‐coordination geometry. Each porphyrin unit links to two neighbouring units to yield a one‐dimensional coordination polymer. These chains are further interlinked by hydrogen bonds to form a two‐dimensional network. The complex shows red photoluminescence emission bands in ethanol solution, which can be attributed to ligand‐to‐ligand charge transfer (LLCT) accompanied by partial metal‐to‐ligand charge transfer (MLCT), as revealed by TDDFT calculations.